2018
DOI: 10.3168/jds.2018-14718
|View full text |Cite
|
Sign up to set email alerts
|

A survey of United States dairy hoof care professionals on costs associated with treatment of foot disorders

Abstract: The objective of this study was to collect information regarding hoof care professionals' billing practices and to gather their opinions about foot disorders and the value of their prevention. Responses were gathered from veterinarians (n = 18) and hoof trimmers (n = 116) through both online and paper survey platforms. Because of the limited number of respondents, veterinarian responses were not further analyzed. Of the 6 foot disorders included in the survey, the treatment cost per case was greatest for toe u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
8
0
4
Order By: Relevance
“…Together, the subject areas Veterinary, and Agricultural and Biological Sciences represent 70% of the publications by subject area. However, we should also emphasize the 131 papers classified as Biochemistry, Genetics, and Molecular Biology, of which five were published during the first half of 2018 viz., (Dolecheck, Dwyer, Overton, & Bewley, 2018;Heringstad et al, 2018;Jacobs, Orsel, Mason, & Barkema, 2018;Weigele, Gygax, Steiner, Wechsler, & Burla, 2018;Wilson-Welder, Nally, Alt, Humphrey, & Olsen, 2018). It demonstrates that studies on foot and claw diseases have been aimed at clarifying the fundamental biological mechanisms underlying these complex diseases in cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Together, the subject areas Veterinary, and Agricultural and Biological Sciences represent 70% of the publications by subject area. However, we should also emphasize the 131 papers classified as Biochemistry, Genetics, and Molecular Biology, of which five were published during the first half of 2018 viz., (Dolecheck, Dwyer, Overton, & Bewley, 2018;Heringstad et al, 2018;Jacobs, Orsel, Mason, & Barkema, 2018;Weigele, Gygax, Steiner, Wechsler, & Burla, 2018;Wilson-Welder, Nally, Alt, Humphrey, & Olsen, 2018). It demonstrates that studies on foot and claw diseases have been aimed at clarifying the fundamental biological mechanisms underlying these complex diseases in cattle.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, it was calculated that the average cost of lameness caused by DD in the US is $132.96 per cow [2]. Among treated foot disorder cases over the past year, a recent study estimated that digital dermatitis was most prevalent (43.9 %) with the mean total treatment costs of $7.5 per case of digital dermatitis [3]. The average cost per cow is considerably larger for the bandaging option and therefore with the treatments showing no difference in healing potential, then there is every reason for a farmer to opt for the cheaper option of scarification and spraying.…”
Section: Discussionmentioning
confidence: 99%
“…Digital dermatitis (DD) can be described as a one of the major global problems in dairy cattle, not only through the incurred financial losses due to its main symptom of lameness but also in terms of the welfare of the animals [3,13], therefore treatment and prevention have an important role worldwide. Described as the "leading cause of lameness in dairy cattle in North America and Europe" [18], it develops typically as a moist, light grey-brown area with erect hairs bordering the lesion, it can be found on the plantar aspect of the foot, just between the bulbs of the heels.…”
Section: Introductionmentioning
confidence: 99%
“…Although DD was not always associated with altered locomotion, studies have found that cattle identi ed with DD lesions were 8 and 10 times more likely to be diagnosed as either lame or moderately to severely lame compared with cattle without lesions, respectively (22). DD was the most treated foot lesion by hoof care professionals in the USA (23). It has been estimated that each case of DD costs $64 -$133 due to treatment costs and production losses (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%